2018
DOI: 10.1371/journal.pone.0194159
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of human papillomavirus (HPV) vaccination in Hong Kong: Facilitators and barriers among adolescent girls and their parents

Abstract: The present study is aimed at assessing the feasibility of delivering the HPV (human papillomavirus) vaccine to girls through a school-based program in Hong Kong, as well as to examine the facilitators and barriers associated with their participation. We approached 1,229 eligible girls aged 9 to 14 at eight schools in Hong Kong to join the program and then delivered the bivalent HPV vaccine at 0 and 6 months over the course of one school year. The students and their parents completed separate questionnaires to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
5
23
2
Order By: Relevance
“…As expected, those considering it dangerous for their children to contract rotavirus gastroenteritis and having positive perception toward the effectiveness of the vaccine were more likely to have immunized their children. These findings are consistent with several studies worldwide evaluating factors positively associated with vaccination [15,17,20,33,34,35]. These observations underlined the importance of not only adequately providing information about rotavirus infection to parents, but also explaining the utility of the vaccination in order to increase the coverage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, those considering it dangerous for their children to contract rotavirus gastroenteritis and having positive perception toward the effectiveness of the vaccine were more likely to have immunized their children. These findings are consistent with several studies worldwide evaluating factors positively associated with vaccination [15,17,20,33,34,35]. These observations underlined the importance of not only adequately providing information about rotavirus infection to parents, but also explaining the utility of the vaccination in order to increase the coverage.…”
Section: Discussionsupporting
confidence: 91%
“…The low coverage rates are still public health challenges and various factors have been cited for why parents and informal caregivers’ declined childhood vaccinations, such as vaccine hesitancy [11,12], lack of appropriate information [13,14], and perception of vaccine safety and benefits [15,16,17]. Therefore, an understanding of the parents’ knowledge, beliefs, and behaviors regarding vaccination against rotavirus could provide useful information on the factors that influence the uptake and to design and to develop interventions to increase the coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents’ and parents’ knowledge and attitudes towards HPV and HPV vaccine are crucial in their decision to vaccinate. [ 16 , 17 ] One systematic review of 25 studies found that vaccine uptake among female adolescents was associated with vaccine-related knowledge, attitudes, information provided by healthcare providers, health insurance coverage, age, and childhood vaccination. [ 18 ] Another systematic review of 28 qualitative studies and 44 surveys reported the consistent finding that adolescents and parents struggled with their decision due to limited information, declining vaccination for concerns over vaccine safety and low perception of risk of HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed an association between parents who did not want their daughters vaccinated and inadequate knowledge regarding the vaccine. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation